Activation of the circAGFG1/miR-195-5p/PD-L1 axis induces lung injury in sepsis - Yang Bi; Rui Ding; Xinyan Liu; Yun He; Xukun Liu; Shouye Ma; Chaofan Wang; Zhongfa Zhang; Xuan Song (Human Cell, 2025)
Severe sepsis can escalate to acute lung injury (ALI), a critical condition with limited treatment options. Emerging research highlights the role of non-coding RNAs, including microRNAs (miRNAs) and circular RNAs (circRNAs), in regulating epithelial and immune cell responses in sepsis-induced ALI. This study delves into the circAGFG1/miR-195-5p/PD-L1 axis to elucidate its potential in this context. The conducted experiments using Th17 cells differentiated from CD4+ T cells isolated from human umbilical cord blood, co-cultured with transfected Calu-3 cells. The assessed cell viability, RNA, and protein expression levels under inflammatory stimuli. In addition, we collected bronchoalveolar lavage fluid and lung tissues from a cecal ligation and puncture mouse model. Quantification of RNA and protein expression of inflammatory and survival markers provided insights into the regulatory mechanisms involved. Peripheral blood samples from sepsis/ALI patients and healthy controls revealed that circAGFG1 expression is significantly downregulated, while miR-195-5p expression is upregulated in patients compared to healthy individuals. In both Calu-3 cells and induced Th17 cells, as well as in sepsis-induced ALI mouse models, the circAGFG1/miR-195-5p/PD-L1 axis was shown to regulate the expression of inflammatory cytokines, Th17 cell differentiation, and markers of epithelial cell survival. Results show the circAGFG1/miR-195-5p/PD-L1 axis plays a critical role in the pathogenesis of sepsis-induced ALI. Targeting this axis could present a novel therapeutic strategy for preventing ALI in sepsis and other conditions characterized by heightened lung inflammation. This research paves the way for new treatment approaches, offering hope for improved outcomes in patients suffering from severe sepsis and ALI. Graphical abstract

CircTBCK protects against osteoarthritis by regulating extracellular matrix and autophagy - Wei Wang; Yuzhe Sun; Peng Tang; Rui Zhang; Yufeng Jiang; Hongwei Min; Chen Gao (Human Cell, 2025)
Osteoarthritis (OA) is a widespread chronic bone and joint disease for which there is currently no effective preventive or therapeutic treatment. Accumulating evidence indicates that circular RNAs (circRNAs), a class of noncoding RNAs, play critical roles in OA. Therefore, in this study, we aimed to reveal an unexplored circTBCK and elucidate its mechanism of action in the pathological process of OA. The different expression of circTBCK was obtained both in vitro and in vivo. In the in vivo model, mice were induced via destabilization of the medial meniscus (DMM) surgery, while in vitro model, mouse cells like primary chondrocytes of newborn mice and ATDC5 cell line were treated with IL-1β treatment (10 ng/mL for 24 h). The level of circTBCK was examined by quantitative real-time polymerase chain reaction (qRT-PCR). After circTBCK was overexpressed or knocked down, IL-1β treatment was performed, and then, chondrocyte viability was detected via a Cell Counting Kit-8 (CCK-8) assay at 0, 24, 48, or 72 h. To assess type II collagen (Collagen II) expression, immunofluorescence (IF) analysis was used. The levels of mRNAs and proteins related to proliferation, the extracellular matrix (ECM) and autophagy were determined by qRT-PCR and Western blotting. Compared with OA treatment, primary chondrocytes with treatment of both circTBCK overexpression and IL-1βincreased the expression of anabolic factors—Collagen II and SRY-box transcription factor 9 (SOX9), proliferation-related molecules—Ki-67 and proliferating cell nuclear antigen (PCNA), and autophagy-related molecules—Microtubule-associated protein 1 light chain 3 (LC3), B-cell lymphoma 1 (Bcl1), and autophagy-related 5 (Atg5) and decreased Sequestosome 1 (SQSTM1 or P62). In contrast, knockdown of circTBCK aggravated the chondrocyte degeneration induced by IL-1β. Overall, our findings suggest that circTBCK, an unexplored circRNA, could regulate autophagy, proliferation, and the extracellular matrix (ECM) to mitigate the development of OA, suggesting a possible target for OA prevention and therapy.

ZC3H13 promotes autophagy in bladder cancer through m6A methylation modification of PJA2 and ubiquitination of KSR1 - Beibei Liu; Mengjie Chen; Yujie Liang; Zhijie Mei; Wei Sun; Wuyue Gao; Tiantian Zhang; Rui Wang; Yuanyuan Guo (Human Cell, 2024)

Nanofiber-based delivery of evodiamine impedes malignant properties of intrahepatic cholangiocarcinoma cells by targeting HDAC4 and restoring TPM1 transcription - Rui Zou; Yiyao Wang; Yaoqing Cai; Zhenming Xing; Yongfu Shao; Duo Li; Chunchun Qi (Human Cell, 2024)

F-box and leucine-rich repeat protein 16 controls tamoxifen sensitivity via regulation of mitochondrial respiration in estrogen receptor-positive breast cancer cells - Feng Chen; Lu Wang; Yanrong Feng; Wenxin Ma; Junqin Liu; Qianyao Bi; Yao Song; Rui Gao; Yanhan Jia (Human Cell, 2023)

Novel insights into tumorigenesis and prognosis of endometrial cancer through systematic investigation and validation on mitophagy-related signature - Rui Sun; Xiaoyu Zhou; Tong Wang; Yao Liu; Lina Wei; Ziyi Qiu; Chunping Qiu; Jie Jiang (Human Cell, 2023)

ZNRF2 as an oncogene is transcriptionally regulated by CREB1 in breast cancer models - Jin-Tao Liu; Zhen-Xuan Sun; Rui Zhong; Yi-Dan Zhang; Teng Wang; Yu-Dong Hou; Jian-Heng Bao; Lei Zhang; Bo Chen (Human Cell, 2023)

TEAD4 predicts poor prognosis and transcriptionally targets PLAGL2 in serous ovarian cancer - Xin Tong; Yi-Si Liu; Rui Tong; Wei-Wei Tang; Xue-Mei Li; Chun-Yan Wang; Yong-Peng Wang (Human Cell, 2023)

Establishment and comprehensive analysis of a new human cell line (NK-NJ) with NK-cell characteristics established from extranodal natural killer cell lymphoma/leukemia - Jin-Hua Liang; Wei-Ting Wang; Kai-Xin Du; Tong-Yao Xing; Yan Wang; Hui Wang; Lu Liu; Rui Guo; Yang Shao; Junheng Liang; Yue Li; Hao-Rui Shen; et al. (Human Cell, 2022)

MiR-100-5p inhibits osteogenic differentiation of human bone mesenchymal stromal cells by targeting TMEM135 - Rui Wang; Miao Zhang; Ying Hu; Juan He; Qiao Lin; Nianchun Peng (Human Cell, 2022)

Long non‑coding RNA PART1: dual role in cancer - Rui Ran; Chao-Yang Gong; Zhi-Qiang Wang; Wen-Ming Zhou; Shun-Bai Zhang; Yong-Qiang Shi; Chun-Wei Ma; Hai-Hong Zhang (Human Cell, 2022)

RIG-I acts as a tumor suppressor in melanoma via regulating the activation of the MKK/p38MAPK signaling pathway - Rui Guo; Shun-Yuan Lu; Jin-Xia Ma; Qian-Lan Wang; Lu Zhang; Ling-Yun Tang; Yan Shen; Chun-Ling Shen; Jin-Jin Wang; Li-Ming Lu; Zhu-Gang Wang; Hong-Xin Zhang (Human Cell, 2022)
Studies have indicated that RIG-I may act as a tumor suppressor and participate in the tumorigenesis of some malignant diseases. However, RIG-I induces distinct cellular responses via different downstream signaling pathways depending on the cell type. To investigate the biological function and underlying molecular mechanism of RIG-I in the tumorigenesis of melanoma, we constructed RIG-I knockout, RIG-I -overexpressing B16-F10 and RIG-I knockdown A375 melanoma cell lines, and analyzed the RIG-I-mediated change in the biological behavior of tumor cells in spontaneous and poly (I:C)-induced RIG-I activation. Cell proliferation, cell cycling, apoptosis and migration were detected by CCK-8 assay, BrdU incorporation assay, Annexin V–PI staining assay and Transwell assay, respectively. In vivo tumorigenicity was evaluated by tumor xenograft growth in nude mice and subsequently by Ki67 staining and TUNEL assays. Furthermore, Western blotting was utilized to explore the underlying mechanism of RIG-I in melanoma cells. Our data showed that RIG-I promotes apoptosis and inhibits proliferation by G1 phase cell cycle arrest in the melanoma cell lines. Mechanistically, RIG-I induced the phosphorylation of p38 MAPK and MAPK kinases MKK3 and MKK4. In conclusion, the current study demonstrated that RIG-I suppressed the development of melanoma by regulating the activity of the MKK/p38 MAPK signaling pathway, which is relevant to research on novel therapeutic targets for this malignant disease.

Serine protease HtrA2/Omi regulates adaptive mitochondrial reprogramming in the brain cortex after ischemia/reperfusion injury via UCP2-SIRT3-PGC1 axis - Hao Meng; Lian-Kun Sun; Jing Su; Wan-Yu Yan; Yao Jin; Xin Luo; Xian-Rui Jiang; Hong-Lei Wang (Human Cell, 2022)

miR-140-3p aggregates osteoporosis by targeting PTEN and activating PTEN/PI3K/AKT signaling pathway - Ruofeng Yin; Jiajia Jiang; Huimin Deng; Zhaobin Wang; Rui Gu; Fei Wang (Human Cell, 2020)